KERAGAMAN GENETIK DAN HERITABILITAS 10 AKSESI CABAI RAWIT (Capsicum frutescens L.) YANG DITANAM DI LAHAN PESISIR - Nur Ain Nadia; Rustikawati; Uswatun Nurjanah; Reny Herawati; Catur Herison (BPFP Universitas Bengkulu, 2025)
[GENETIC VARIABILITY AND HERITABILITY OF 10 ACCESSIONS OF BIRD’S EYE CHILI (Capsicum frutescens L.) GROWN ON COASTAL LAND]. Cultivation of bird’s eye chili (Capsicum frutescens L.) on saline coastal land in Indonesia faces several environmental constraints. Efforts to increase bird’s eye chili productivity in saline land are by planting varieties that are adaptive to stressed environmental conditions. This research aims to evaluate performance, estimate genetic diversity and heritability of agronomic traits in 10 bird’s eye chili accessions in coastal land in Kuala Alam, Bengkulu. The research was conducted using a one-factor Randomized Complete Block Design (RCBD) with 10 accessions as treatments and three replications. The results showed that the characters of plant height, stem diameter, flowering date, dichotomous height, fruit length and fruit diameter had wide genotypic variation. Broad phenotypic was shown by all characters. High heritability values were obtained in the characters of plant height, stem diameter, flowering date, dichotomous height, number of dichotomous points, fruit length and fruit diameter. The characters of number of leaves, leaf greenness, number of fruits per plant and fruit weight per plant have medium heritability values. The number of stomata and stomatal density characters have low heritability values. Accession Bangka 2 has superior performance in the characters of plant height, stem diameter, flowering date, dichotomous height, number of dichotomous point, fruit length, fruit diameter and fruit weight per plant. Accessions with superior performance and characters that have high heritability values with a wide genotypic and phenotypic range are used as elders in plant breeding programs. These findings form the basis for the development of superior bird’s eye chili varieties that are adaptive to saline land. Full text pdf